Congenital distichiasis: Histopathological report of 3 cases - Alkatan, Hind Manaa; Galindo-Ferreiro, Alicia; Maktabi, Azza; Galvez-Ruiz, Alberto; Schellini, Silvana [UNESP] (Wolters Kluwer, 2017)
Distichiasis is a condition clinically presenting as partial or complete accessory row of lashes that emerges from the meibomian glands orifices. It can be an acquired or congenital with an autosomal dominant inheritance. The histopathological features are not well described in the ophthalmic literature, however they include abnormal pilosebaceous units within the posterior lamella of the eyelid and perifollicular chronic inflammatory cell infiltration. In this report, we describe the histopathological findings of three congenital distichiasis cases treated at King Khaled Eye Specialist Hospital (KKESH), Riyadh, Saudi Arabia with discussion on the pathogenesis of such a condition and the differentiating features from ectopic cilia.
Keywords: Cilia; Congenital; Distichiasis; Eyelid; Histopathology